Student decision making process on the purchase of newspaper in Klang Valley and Selangor: (Case study on KOSMO! newspaper) / Nabil Fikri Hussin (Faculty of Business Management, 2007)
This is a research on student decision making process on the purchase of newspaper and it case study is on Kosmo! newspaper. This research will focus on the Process stage of consumer decision making process. In Process stage, there are three elements that consumers involved in the process. That is Need Recognition, Prepurchase Search and Evaluation of Alternatives. There are three Research Questions in this research. First, what is the type of need that consumers involved in Need Recognition, is it Desired Need and Actual Need? This research will identify which type of need that associate with them when they make decision to purchase newspaper. Second, in Prepurchase Search, from where do the consumers gather the information, is it from Past Experience or from the Promotional Activities? This research will find out which source is consumers more preferred when they gather information about the newspaper they intend to purchase. Third, is there any relationship between Evaluation of Alternatives elements: that is Lifestyle, Criteria Used to Evaluate Brand and Evoked Set? This research will identify the relationship of those three elements and their influences to consumers when they evaluate the alternatives that are best for them. From the interpretation of the data, it answered the research questions. In Need Recognition stage, newspaper purchase is a desired need and consumers are more preferred to gather information from Promotional activities in Prepurchase Search stage. And finally, in evaluation of alternatives, consumers select brand based on their Lifestyles, Criteria Used to Evaluate Brand and Evoked Set.